Developing Interactive Media with Articulate Storyline 3 for Enhancing Students’ Learning Motivation on Newton’s Laws - Nuranisa, Fadillah Eka; Purwanto, Andik; Risdianto , Eko (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2024)
The learning motivation of grade XI students of SMAN Bengkulu still needs to be improved. This can be seen from the analysis of student needs that were previously carried out with the results that there are still many students who do not understand physics material because they are still lacking in the use of software-based media. This study aimed to determine the development of Articulate Storyline-assisted media to increase students' motivation to learn Newton's law material. Research and development is a type of research that is being carried out (Research and Development). This study used the ADDIE model. This model consists of stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of the study were 33 students in grade XI.2 of SMAN Bengkulu. Data analysis included analysis of learning implementation, media feasibility, student response, and student learning motivation. The results of the research showed: (1) The results of the media feasibility test by the three validators obtained an average percentage value of 85.30% which shows that this learning media is very feasible to use. (2) In the results of the student response, a score of 86.56% was obtained so it was classified as very good. (3) In the results of student learning motivation in the initial motivation with a percentage of 73.86% with the category